2021
DOI: 10.1097/md.0000000000026914
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency and cryoballoon ablation improve cognitive function in patients with atrial fibrillation

Abstract: Atrial fibrillation is considered to be the most common arrhythmia in the clinic, and it gradually increases with age. In recent years, there has been increasing evidence that atrial fibrillation may exacerbate the progression of cognitive dysfunction. The current guidelines recommend ablation for drug-refractory atrial fibrillation. We aimed to prospectively analyze changes in cognitive function in patients with atrial fibrillation following treatment using different ablation methods. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The study scores ranged from 6/9–9/9. The cohort studies [ 14 19 ] presented suitable cohort comparability and outcome assessments, though often failed to demonstrate that the outcome of interest (dementia or impaired cognitive function) was not present at the start of the study. Jin et al fulfilled all domains appropriately [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study scores ranged from 6/9–9/9. The cohort studies [ 14 19 ] presented suitable cohort comparability and outcome assessments, though often failed to demonstrate that the outcome of interest (dementia or impaired cognitive function) was not present at the start of the study. Jin et al fulfilled all domains appropriately [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this systematic review and meta-analysis, 4 studies ( 24 27 ) were retrospective cohort studies and 9 ( 28 36 ) were controlled clinical trials. Six studies ( 26 , 30 – 32 , 34 , 35 ) were conducted in China, 2 ( 24 , 29 ) in South Korean, 2 ( 25 , 27 ) in the United States, 1 ( 28 ) in Germany, 1 ( 36 ) in Japan, and 1 ( 33 ) in Australia. Four studies ( 24 27 ) reported the incidence of new-onset dementia, 4 ( 28 – 31 ) reported the changes in MoCA score, 3 ( 28 , 35 , 36 ) reported the MMSE score, 1 ( 32 ) reported the TICS-m score, and 2 ( 33 , 34 ) reported the incidence of POCD.…”
Section: Resultsmentioning
confidence: 99%
“…A small prospective study enrolling 23 patients showed worse neuropsychological outcomes in verbal memory in the AF ablation group ( 37 ). Previously, new SCLs detected after CA were a common occurrence in magnetic resonance imaging (MRI) of the brain and were reported in 4.3–38.9% of patients ( 32 , 38 , 39 ). However, during MRI follow-up of more than 90% of patients 1 year after AF ablation, SCLs had been proven to be resolved ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following supporting information can be downloaded at: , Study selection; Data extraction; Table S1 : PRISMA 2020 checklist; Table S2 : Newcastle-Ottawa quality assessment scale table for cohort studies. [ 17 , 18 , 21 , 46 , 47 , 48 ] are cited in the Supplementary Materials .…”
mentioning
confidence: 99%